Phytochemical Profiling and TLC Analysis of Hymenocardia acida Methanol Leaf Extract - Zubair, Abdulgafar Omeiza (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The study investigated the phytochemical constituents and chromatographic profile of Hymenocardia acida leaf extract obtained through methanol extraction. Hymenocardia acida, widely used in traditional medicine across Africa, is reputed for its therapeutic potential in treating various ailments. To explore the bioactive compounds, we conducted a series of qualitative phytochemical screenings to detect the presence of alkaloids, flavonoids, saponins, tannins, phenols, terpenoids, steroids. The results revealed a broad spectrum of phytochemicals known to exhibit antioxidant, antimicrobial, and anti-inflammatory properties. Additionally, thin-layer chromatography (TLC) was performed to obtain a chromatographic profile of the methanol extract, aiming to separate and identify potential bioactive compounds. Silica gel plates were used as the stationary phase, and various solvent systems, such as hexane acetate and chloroform were optimized for effective separation of phytochemicals. The resulting TLC plates were analyzed under UV light at 254 nm and 365 nm, and retention factor (Rf) values were calculated to provide preliminary identification. Different solvent systems were used which showed different behaviors in the plant compounds. The resulting mixture between hexane and ethyl acetate at ratio 9:1, 8:2, 7:3, 6:4 and 5:5 are given as (0), (0,0.26,0.16), (0,0.95,0.94), (0) and (0,0.91,0.95) respectively. The TLC fingerprint and phytochemical profile generated from this study offer valuable insights into the potential pharmacological applications of Hymenocardia acida, supporting its use in traditional medicine and guiding further isolation and characterization of its active compounds for drug development.